Correction of Valve Desease in Combination of Aorto-Coronary Bypass - Popov, V. V.; Kupchinsky, A. V.; Solomka, S. N.; GurtovenkoА. N.; Hripachenko, A. I.; BolshakА. А.; Tykhonenko, L. I.; Pukas, K.; Klimenko, L. A. (Ukrainian Journal of Cardiovascular Surgery, 2016)
Purpose of work is a study of possibilities of retrograde cardioplegia at the correction of valve disease in combination with aortocoronary bypass. In an analysable group were included 75 patients. 45 (60.0%) men and 30 (40.0%) women in the average age 64.7±6.3 years. All patients belong to IY functional class of New York classification (NYHA). All patients underwent valve replacement + aorto-coronary bypass. Myocardial protection was carried out in the conditions of permanent crystalloid cardioplegia of Custadiol. Among 75 operated patients on the hospital stage died 1 (hospital mortality 1.4%). Cases of death was bleeding. Inotropic support (dobutaminum) during the early postoperative period made in limits – 3–4 mkrg/min/kg within the first 48 hours. Level of enzymes of group MV-KFK for the second day after operation (U/l) was not equal in all groups. The correction of valve disease+ aorto-coronary bypass with usage of retrograde cardioplegia allows adequately protect myocardium.